The Reduviidae (Hemiptera: Heteroptera) of Ipassa Reserve (Makokou, Gabon) - Guilbert, Eric; Chłond, Dominik (Zootaxa, 2009)
In the frame of global and rapid inventories of biodiversity, a first inventory of the Reduviidae of the Ipassa Reserve in Makokou, Gabon is done, including recent field surveys as well as information from museum collections. A total of 42 species, including 27 newly recorded from Ipassa Reserve and 16 also newly recorded from Gabon, are listed. Their distributions, and a general discussion on the geographical distributions of the species, are discussed.